When environmental variation short-circuits natural selection - Kruuk, L; Merila, J; Sheldon, B (2003)
The development of a coherent framework for measuring natural selection was one of the major advances in evolutionary biology in the 1970s and 1980s. However, for evolution to occur, natural selection must act on underlying genetic variation, whereas most measurements of natural selection are limited to phenotypes. Two new papers now show that environmentally induced covariances between phenotypes and fitness can frequently lead to the systematic overestimation of the strength of natural selection.